2005
DOI: 10.1007/s00415-005-0945-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesteryl ester transfer protein (CETP) polymorphism modifies the Alzheimer's disease risk associated with APOE ε4 allele

Abstract: Cholesterol regulates the production of amyloid beta (Abeta), which is central to the pathogenesis of Alzheimer's disease (AD), with high cellular cholesterol promoting and low cellular cholesterol reducing Abeta in vitro and in vivo. High density lipoprotein (HDL) plays a central role in the removal of excess cholesterol from cells, and cholesteryl ester transfer protein (CETP) is a crucial protein involved in the regulation of HDL levels. Two common polymorphisms in the promoter region (C-629A) and exon 14 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 29 publications
5
46
0
3
Order By: Relevance
“…The CETP C-629A and TaqI B polymorphisms have been studied with respect to AD. A study in a Spanish population of the relationship between the CETP C-629A and I405V polymorphisms and the APOE*4 allele indicated that the CETP gene modifies AD risk possibly through modulation of brain cholesterol metabolism [17]. This modification effect was seen only for the C-629A polymorphism and not for the I405V.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CETP C-629A and TaqI B polymorphisms have been studied with respect to AD. A study in a Spanish population of the relationship between the CETP C-629A and I405V polymorphisms and the APOE*4 allele indicated that the CETP gene modifies AD risk possibly through modulation of brain cholesterol metabolism [17]. This modification effect was seen only for the C-629A polymorphism and not for the I405V.…”
Section: Discussionmentioning
confidence: 99%
“…While one previous study [17] showed evidence that the C-629A polymorphism of the CETP gene modifies the risk of AD in association with the APOE gene by reducing the risk of AD, another study found no effect of this gene on the disease [18]. We studied the I405V polymorphism of the CETP gene in relation to AD in a large population-based study and investigated whether this polymorphism is independently associated with AD, or acts in concert with the APOE gene in conferring risk for the disease.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, in fibroblasts from AD patients ACAT-1 mRNA levels are increased significantly. Recent genetic evidence associates a single nucleotide polymorphism (SNP, codon 405 isoleucine to valine (V405)) of the cholesterol ester transfer protein (CETP) with the lowered risk of dementia [65,66]. Similar to what was first noted by Alzheimer, ultrastructural studies on autopsied brain tissue from Alzheimer's disease patients using immunocytochemistry with an antibody that recognizes amyloid-beta peptides revealed cytosolic clusters of lipid droplets in immunopositive areas and there are cytosolic granules [67].…”
Section: Cholesterol and Cholesterol Estersmentioning
confidence: 61%
“…APOE epsilon4 carriers that were homozygous for the CETP -629A allele had approximately a threefold lower risk of developing AD than the carriers of the -629C allele (69). These data suggest that CETP behaves as a modifier gene for AD risk associated with the APOE epsilon4 allele.…”
Section: Alzheimer's Disease Riskmentioning
confidence: 77%
“…Ha and Barter (3) reported that CETP is present in fish, reptiles, birds, and mammals, but not in rats and mice. Chemical purification showed that CETP is a plasma glycoprotein consisting of 476 amino acids with an apparent molecular weight of [66][67][68][69][70][71][72][73][74]. This discovery led to subsequent cDNA cloning and tissue expression studies (5).…”
Section: Brief Highlights Of Cetp Historymentioning
confidence: 99%